Erinea formation on Quercus ilex leaves: anatomical, physiological and chemical responses of leaf trichomes against mite attack. - Karioti, Anastasia; Tooulakou, Georgia; Bilia, Anna Rita; Psaras, George K.; Karabourniotis, George; Skaltsa, Helen (Phytochemistry, 2011)
Structures on the surfaces of leaves, such as dense layers of non-glandular trichomes, strongly affect phylloplane mite activities. On the other hand the feeding of eriophyoid mites on leaf surfaces can cause hyperplasia of leaf trichomes (erinea formation). In many cases the hyperplasia is accompanied by the accumulation of pigments within trichome cells, causing an impressive red-brown colouration of the erineum. There is no information, however, on the structure of these pigments as well as on the chemical alterations in the phenolic content of plant trichomes in response to mite attack. Erinea formation on the abaxial surface of Quercus ilex leaves upon Aceria ilicis (Acari: Eriophyoidea) attack provides an excellent model on this topic. Differences in the structure and chemical composition of isolated trichomes derived either from healthy (normal trichomes) or mite attacked (hypertrophic trichomes) leaves were examined. Carbon investment was comparable between the two different trichome types, but the cell walls of the hypertrophic trichomes appeared thinner and did not contain microcrystalline cellulose. Observations under the fluorescence microscope showed that the emitted fluorescence was different between the two trichome types, indicating a different composition in fluorescencing phenolic compounds. The chemical analyses confirmed that hypertrophic trichomes contained higher concentrations of the feeding deterrents proanthocyanidin B3 and catechin, as well as of quercetin-3-O-glucoside, but lower concentrations of acylated flavonoid glycosides, than the normal ones. The results showed that the structural and functional changes in leaf trichomes upon mite attack may be an effort of the leaf to compensate the damage caused by the pest.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21131012
Keywords: Fagaceae; Leaf trichomes; Mites; phenolics; Quercus ilex

The ability of abaxial and adaxial epidermis of sun and shade leaves to attenuate UV-A and UV-B radiation in relation to the UV absorbing capacity of the whole leaf methanolic extracts - Liakoura, Vally; Bornman, Janet F.; Karabourniotis, George (Physiologia Plantarum, 2003)
The UV-absorbing capacity (measured as A310 cm−2 and A365 cm−2 or AUVR cm−2) of the shade leaves of four representative evergreen sclerophylls of the Mediterranean region (Quercus coccifera, Q. ilex, Arbutus andrachne and A. unedo) was considerably lower than the corresponding one of sun leaves of the same species. However, fibre optic microprobe measurements showed that adaxial as well as abaxial epidermis of shade leaves of all examined plants, except abaxial epidermis of A. andrachne, were almost as effective as the corresponding ones of the sun leaves in screening out most of the incident UV-B radiation. There is probably a threshold, under which the concentration of the UV-B absorbing compounds in the protective tissues is not furthermore reduced, in spite of the low levels of the stress factor (UV-B radiation) in the environment. On the other hand, the ability of both abaxial and adaxial epidermis to attenuate UV-A radiation, except of adaxial leaf epidermis of Quercus species, depended on the UV absorbing capacity of the whole-leaf extracts, with different correlation patterns between the two Quercus species and the two Arbutus species. This could be explained by the fact that shade leaves showed not only quantitative, but also qualitative differences (higher A310/A365 ratio) in the absorbance of their methanolic extracts compared to these of sun leaves. The results of the present study showed that we should not always correlate the depth of penetration of UV radiation into sun and shade leaves according to the corresponding UV absorbing capacity of the whole leaf methanolic extracts, without taking into account all the anatomical, developmental and biochemical (such as different composition and distribution of the UV-absorbing compounds among the different protective tissues) peculiarities of the leaves of each species.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: abaxial epidermis; adaxial epidermis; Sun and shade leaves; uv absorbing compounds (voyant); UV-A and UV-B radiation

Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F. (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
The following values have no corresponding Zotero field: publisher: Munksgaard International Publishers
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers

Penetration of UV-A, UV-B and blue light through the leaf trichome layers of two xeromorphic plants, olive and oak, measured by optical fibre microprobes - Karabourniotis, George; Bornman, Janet F (Physiologia Plantarum, 1999)
Quartz fibre-optic microprobes were used to monitor the light microenvironment beneath trichome layers of the xeromorphic leaves of two Mediterranean evergreen sclerophylls, Olea europaea and Quercus ilex. Young developing leaves of both plants were densely pubescent on both surfaces of the lamina, whereas the mature leaves were pubescent only on the abaxial side. Trichome layers of young as well as of mature leaves of both plants attenuated almost all incident ultraviolet (UV)-B (310 nm) and UV-A (360 nm) radiation and a considerable portion of blue light (430 nm). Abaxial trichome layers of young leaves were more effective in screening out the incident radiation compared to the adaxial ones of the same leaves and also compared to the abaxial layer of the mature leaves. The abaxial epidermis of dehaired mature leaves of O. europaea was ineffective in absorbing most of the incident UV-B and UV-A radiation. UV and visible spectra beneath trichome layers of O. europaea in mature leaves confirmed that the light microenvironment on the epidermis was deprived in the UV-B, UV-A and partly in the blue spectral regions. It is proposed that the occurrence of a dense trichome layer, especially in young leaves, may play a protective role against not only UV-B radiation damage, but also against high visible irradiance. This function is performed irrespective of the differing anatomy of individual hairs of both plants. The protection provided by the trichomes could afford advantages under stress conditions, especially during leaf development.
Keywords: Abaxial; Adaxial (voyant); leaves; light; trichome layers

The dense indumentum with its polyphenol content may replace the protective role of the epidermis in some young xeromorphic leaves - Karabourniotis, George; Fasseas, Costas (Canadian Journal of Botany, 1996)
The bright, yellow-green, ammonia-induced fluorescence of polyphenol compounds contained in the nonglandular hairs and within the epidermis of Olea europaea and Quercus ilex leaves was age dependent. Epifluorescence microscopic examination of transverse sections of leaves from both species showed that abaxial and adaxial epidermal layers emitted the characteristic green-yellow bright fluorescence only in late developmental stages, when a considerable decrease of the trichome density had already occurred. At earlier developmental stages, only the dense and thick trichome layer emitted the bright green-yellow fluorescence. In addition, the trichomes of young leaves of Olea and Quercus resembled the glandular ones of other species morphologically and possibly functionally. These findings suggest that the protective role of the trichome against ultraviolet-B radiation damage and (or) other environmental factors is particularly significant during the early stages of leaf development and may be less important at later stages, when the protective role is taken over by the epidermis. Keywords: leaf hairs, phenolics, UV-B radiation damage, leaf development, Olea europaea L., Quercus ilex L.
doi: 10.1139/b96-043doi: 10.1139/b96-043The following values have no corresponding Zotero field: publisher: NRC Research Press
Keywords: leaf development; leaf hairs; Olea europaea L.; phenolics; Quercus ilex L.; UV-B radiation damage

The dense indumentum with its polyphenol content may replace the protective role of the epidermis in some young xeromorphic leaves - Karabourniotis, George; Fasseas, Costas (Canadian Journal of Botany, 1996)
The bright, yellow-green, ammonia-induced fluorescence of polyphenol compounds contained in the nonglandular hairs and within the epidermis of Olea europaea and Quercus ilex leaves was age dependent. Epifluorescence microscopic examination of transverse sections of leaves from both species showed that abaxial and adaxial epidermal layers emitted the characteristic green-yellow bright fluorescence only in late developmental stages, when a considerable decrease of the trichome density had already occurred. At earlier developmental stages, only the dense and thick trichome layer emitted the bright green-yellow fluorescence. In addition, the trichomes of young leaves of Olea and Quercus resembled the glandular ones of other species morphologically and possibly functionally. These findings suggest that the protective role of the trichome against ultraviolet-B radiation damage and (or) other environmental factors is particularly significant during the early stages of leaf development and may be less important at later stages, when the protective role is taken over by the epidermis. Keywords: leaf hairs, phenolics, UV-B radiation damage, leaf development, Olea europaea L., Quercus ilex L.
doi: 10.1139/b96-043
Keywords: leaf development; leaf hairs; Olea europaea L.; phenolics; Quercus ilex L.; UV-B radiation damage

UV-B protective potential and flavonoid content of leaf hairs of Quercus ilex - Skaltsa, Helen; Verykokidou, Evmorphia; Harvala, Catherine; Karabourniotis, George; Manetasi, Yiannis (Phytochemistry, 1994)
Flavonoids of non-glandular leaf hairs from Quercus ilex were analysed. The main compounds were acylated kaempferol glycosides. Acylation shifted the absorption peak into the ultraviolet-B region of the spectrum in which intact trichome layers absorbed strongly. Ultraviolet-B radiation caused a considerable reduction of photosystem II photochemical efficiency only in dehaired leaves. It is suggested that leaf hairs, besides other roles, may function as an effective filter against the harmful ultraviolet-B radiation.
Keywords: Fagaceae; flavonoids; Holly Oak; leaf hairs; Quercus ilex; UV-B damage